A criança, o jovem, a mulher e a voz narrativa em romances de José J. Veiga - Gomes, Analice de Sousa (2017)
The present study, of an analytic-interpretative nature, aims to make considerations about the representation of the ex-centric man immersed in a context of fear and domination in the novels by J.J. Veiga, produced and published between 1964 and 1982, establishing relations between the sociopolitical events that occurred in Brazil during this period and the fictional construction of the author. This representation of the marginalized man, in this research, it is analyzed from the figures of the child, the young, the woman and the speech of the narrative voice that builds environments of contestation and designates voice to the characters that constantly question about the meaning of the human existence in a world of relations and values coined by the search for power and its maintenance. The focus on the child it is in its ability to overcome obstacles pointing to the maturation and development of a critical reality view in which it is inserted. The young, however, closer to the relationships of the adult world, shows that it is fragile in the face of frustrations, and finds itself disillusioned thinking of its future. The woman it is seen from a double perspective: domination and freedom. On the one hand, it is dominated by patriarchal precepts, believing that it must fulfill the "woman's role"; closes to the indoor environment of the house and it is dedicated to the housework. On the other hand, a little more liberated from the domination of patriarchy, domestic boundaries are advanced and inserted into the political and social contest, which seen the main elements of oppression and segregation. These women bring, in their actions and voices, the resonance of the achievements of the feminist movements. The narrative voice has a denunciative role. The veigueanos narrators, reveal the existential conflicts caused in the people times of oppression, but, therefore, it highlights hope as a motivation for the transformation of reality and the (re) appropriation of freedom and the identity of being. In this context, the analysis revolves around characters and their search for the existence meaning, as well as the questioning about the reality that oppresses controls and censors. So, for this study, we intend to understand the history of oppression from viewing of the oppressed and to observe the man as the core in the narratives. A hora dos ruminantes, 1966; Sombras de reis barbudos, 1972; Os pecados da tribo, 1976 and Aquele mundo de Vasabarros, 1982 based on assumptions that emphasize the representation of ex-centric characters and on the criticism already produced on the fiction of José J. Veiga. For this, the work is guided by the authors' reflections like Linda Hutcheon (1991), José Fernandes (1986),Simone de Beauvoir (1970), Agostinho Potenciano de Souza (1990), Tieko Miyazaki (1988), Maria Zaira Turchi (2003/2005), Flávio Kothe (1986), Tânia Pellegrini (1996), Vânia Maria Resende (1988), Pierre Bourdieu (2002), between others.